2015
DOI: 10.1007/s10096-015-2412-z
|View full text |Cite
|
Sign up to set email alerts
|

A multiplex real-time PCR assay for routine diagnosis of bacterial vaginosis

Abstract: A semi-quantitative multiplex PCR assay for the diagnosis of bacterial vaginosis (BV) was evaluated in a prospective study in a population of Dutch women with complaints of abnormal vaginal discharge. The PCR targets Gardnerella vaginalis, Atopobium vaginae, Megasphaera phylotype 1, Lactobacillus crispatus and Lactobacillus iners. Together with a short questionnaire, a vaginal swab for PCR and vaginal smear for microscopy were taken by their general practitioner or gynaecologist. Data from 151 women (median ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
54
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 67 publications
(68 citation statements)
references
References 22 publications
9
54
0
2
Order By: Relevance
“…G. vaginalis, A. vaginae, M. hominis and Mobiluncus spp. were detected at higher concentrations in vaginal microbiota of BV compared to non-BV women, corroborating the findings of recent studies [3,24,30,33,38]. In contrast, Lactobacillus spp.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…G. vaginalis, A. vaginae, M. hominis and Mobiluncus spp. were detected at higher concentrations in vaginal microbiota of BV compared to non-BV women, corroborating the findings of recent studies [3,24,30,33,38]. In contrast, Lactobacillus spp.…”
Section: Discussionsupporting
confidence: 90%
“…A recent study has investigated the community structure of healthy and BV vaginal microbial ecosystems and detected A. vaginae only in BV group [25]. However, other studies that also investigated microbial communities associated with BV showed results that corroborate our findings [23,24].…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations